Pharmacy Inventory System Design Using Agile Methods - Atika, Frisi; Irwan, Deddy (Al'adzkiya International of Computer Science and Information Technology (AIoCSIT) Journal, 2020)
Currently, the information system has been used by many companies / agencies in Indonesia. All activities will be properly managed by the system, so that they will be more effective and efficient. And now, pharmacies also need systems that can control data properly. Every day there are people who need medicine, therefore pharmacies can be used as a profitable business ingredient. The pharmacy business must have a good system, so that the business can move forward and get a large turnover. The purpose of this study is to assist the pharmacy in processing data on incoming and outgoing stock data so that it will make it easier for the warehouse admin to provide the information needed. In developing this system the researchers used the Agile Software Development method where this method is used to develop systems in the short term that require rapid adaptation and development to changes in any form. The result of this research is the development of sInventory information system at pharmacies that can display drug data, drug stock, sales, expenses, purchase of goods, profit and loss, reports in real time. Keyword : Information Systems, Pharmacy, Agile Method